2016
DOI: 10.1155/2016/9249401
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant LncRNA Expression Profile in a Contusion Spinal Cord Injury Mouse Model

Abstract: Long noncoding RNAs (LncRNAs) play a crucial role in cell growth, development, and various diseases related to the central nervous system. However, LncRNA differential expression profiles in spinal cord injury are yet to be reported. In this study, we profiled the expression pattern of LncRNAs using a microarray method in a contusion spinal cord injury (SCI) mouse model. Compared with a spinal cord without injury, few changes in LncRNA expression levels were noted 1 day after injury. The differential changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
1
28
1
Order By: Relevance
“…Noncoding RNAs such as circulating microRNAs have been found out to be markedly increased in the serum relative to the severity of ASCI, which may be promising biomarkers for diagnose and predicting the severity of ASCI [22]. By using a microarray method in a contusion SCI mouse model, a dynamic lncRNA-mRNA network containing 264 lncRNAs and 949 mRNAs has been constructed to illuminate the interactions between the lncRNAs and mRNAs [23], verifying the differential expression of lncRNAs in contusion SCI. In this study, lncRNA DGCR5 was found to be down-regulated in ASCI.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding RNAs such as circulating microRNAs have been found out to be markedly increased in the serum relative to the severity of ASCI, which may be promising biomarkers for diagnose and predicting the severity of ASCI [22]. By using a microarray method in a contusion SCI mouse model, a dynamic lncRNA-mRNA network containing 264 lncRNAs and 949 mRNAs has been constructed to illuminate the interactions between the lncRNAs and mRNAs [23], verifying the differential expression of lncRNAs in contusion SCI. In this study, lncRNA DGCR5 was found to be down-regulated in ASCI.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that lncRNA expression was highly dynamic across different stages. Nonetheless, these studies have aimed to reveal the lncRNA profiles in different post‐injury time‐points, from immediate, acute, subchronic to chronic phases after SCI (Figure ). These studies provided preliminary views on stage‐specific lncRNA modulation.…”
Section: Lncrna Expression Profiling In Scimentioning
confidence: 99%
“…1). For example, Ding et al [21] found that few changes in lncRNA expression levels were noted 1 day after injury, and significant differential changes in lncRNA expression peaked 1 week after SCI and subsequently declined until 3 weeks after injury. In another study, Zhou et al [22] used microarray analysis and found that 772 lncRNAs were identified as changed in a rat model for 2 h after SCI.…”
Section: Scimentioning
confidence: 99%